SANCTIONS AND THEIR IMPACT ON THE IRAN’S ECONOMY - M. Rahimian (Publishing House of the State University of Management, 2019)
In period, following the imposition of sanctions, Iran faced many economic problems. Financial sanctions did not allow Iran to access international business, and international credit cards system (MasterCard and VISA) was not extended to Iran. The ways of independent development of Iran, used at the moment and possible in the future have been considered in the article. Of possible alternatives, in particular, the concept of development, based on the forecast, that sanctions have a negative impact on Iran, in accordance with the second, sanctions have a positive impact on Iran, have been analyzed. The author examines in the article both concepts and their impact on the country’s economy.